"Nobody Really Knows What We Do": Exploring the Organizational and Occupational Identification of Academic Librarians. Issue 5 (3rd September 2021) - Ishii, Kumi; Markman, Kris M.; Arnow, Hannah; Carr, Sabrina
ABSTRACT: This study investigates the organizational and occupational identification of academic librarians. Results from 21 semi-structured interviews with librarians with instruction roles at an Ivy-league and two state universities reveal that academic librarians identify primarily with their occupation rather than organization. In addition, communication partner as well as two types of identity cues influence participants' communicative strategies during the process of identification. Consistent with communication accommodation theory, in-group or out-group status is triggered by stereotypes, which affects participants' accommodation or nonaccommodation decisions. Unlike previous studies, we find that perceived external prestige can serve as a negative cue limiting the amount of identification in a certain context. Other findings and implications are also discussed.